Thermal and burial history of the axial Arcabuco-Floresta segment, Eastern Cordillera basin, Colombia: evidence from low-temperature thermochronology and numerical modelling - Sandoval-Espinel, John Jairo; Sandoval-Espinel, Leidy Carolina; Bermúdez, Mauricio A.; Bernet, Matthias; Kohn, Barry; Amaya, Sergio; Villamizar-Escalante, Nicolas; Zuluaga, Carlos (Frontiers in Earth Science, 2024)
The axial Arcabuco-Floresta segment of the Eastern Cordillera basin, Colombia exhibits a complex geological history characterized by both along and across strike variations in deformation and exhumation, as well as magmatic activity, all of which provide valuable insights into the broader tectono-thermal evolution of the Andean region. In this study, we combine existing thermochronological data, with 16 new zircons (U-Th)/He and 9 new fission-track dates, and numerical modeling to investigate the thermal history in response to such anomalies across the axial Arcabuco-Floresta segment. Single grain ZHe data from Devonian to Lower Cretaceous strata range from 74 to 20 Ma. ZFT data from the same samples show a broader age distribution ranging from 200 to 70 Ma. The integration of different inverse modeling approaches suggests that cooling, here interpreted as exhumation, occurred in three distinct episodes which can each be linked to different regional tectonic interactions since the Late Cretaceous. Over this time, exhumation commenced in the northern and western parts of the basin and extended progressively through to the eastern and southern parts. The first episode, from the Late Cretaceous to Eocene is related to the accretion of different oceanic terranes related to Farallon Plate. The second, from the Oligocene to Middle Miocene, is interpreted as a probable compressional response to accretion of the Panamá-Chocó Arc, Nazca Plate and the Gorgona Terrane. The third, extending from the Middle Miocene to Pleistocene, may be associated with exhumation driven by far-field deformation resulting from the final collision phase of the Panamá-Chocó block with South America and its interaction with the Nazca and Caribbean plates. This last phase led to the complete emergence of the Eastern Cordillera and its development as an orographic barrier. No evidence was found suggesting any possible influence of thermal overprinting on the thermochronological data in the basin.